To Find Association Between Neck Disability in Relation to Physical Activity Among Young Adults with Chronic Neck Pain - Saraf, Amit; Chauhan, Nishank; Agarwal, Prakhar; Yadav, Kapil; Singhal, Ayush (Asian Journal of Medical Research, 2022)
Background: Neck pain is one of the chief musculoskeletal disorders that is noted in adult population and affect approximately about 14-71% during their lifetime. Neck pain is a very common problem in the society, this is because as it causes discomfort to the individual due to pain. It also is associated with disability that impairs the quality of life. Although, neck pain is very common source of disability, a little is known about its prevalence and course. There has been a rapid advancement of technology in last past ten years, which has drastically affected the lifestyle of the general population. In this view we decided to study the association of neck disability in relation to physical activity in young adults with chronic neck pain. Subjects and Methods: Total 312 cases were taken with chronic neck pain aged between 18-35 years and were divided into 5 groups based on their physical activity. Neck Disability Index score was calculated for each case after asking neck disability index questionnaire. Results: Our result showed that Chronic neck pain was recorded more in 18-25 age group that is 59.6% and Females (52.9%) were more affected with chronic neck pain than males 47.1%. There was significant association between neck disability and radiculopathy. There is no association between the neck disability and the physical activity in the cases with chronic neck pain. Overall statistical non-significant result was observed using Chi square test as the p-value was 0.303. Conclusion: There was no association found between neck disability and physical activity, there was a positive association between neck disability and radiculopathy.